The relationship between body image, eating disorders risk, and the professional help-seeking attitudes of college students in Vietnam - Nguyen, Huan Thanh; Nguyen, Nhi Ngoc Yen; Le, Tran Bao; Le, Pha Cam; Nguyen-Duong, Bao-Tran (Journal of Asian Scientific Research, 2024)
This study investigates the relationship between body image, eating disorder risk, and the professional help-seeking attitudes of college students in Vietnam. We conducted a study with 232 college students (166 females and 66 males). The Attitudes Towards Professional Help-Seeking (ATSPPH), the Eating Attitudes Test (EAT-26), and the Body Shape Questionnaire (BSQ) served as the foundation for the questionnaire. In order to evaluate this research, the PLS-SEM approach was utilized. The results demonstrate that (i) body image, in particular, has a strong and positive link with eating disorder risk; (ii) professional help-seeking attitudes are strongly correlated with body image; (iii) there is a positive correlation between eating disorder risk and professional help-seeking attitudes; and (iv) eating disorder risk will mediate the relationship between body image and professional help-seeking attitudes. This article highlights a relationship between body image preoccupation and professional help-seeking attitudes through mediated eating disorder risk. It is necessary to identify individuals at risk of eating disorders and then consider and devise appropriate strategies to overcome or minimize binge eating or frequent or planned skipping meals; early intervention will reduce the risk of developing an eating disorder. The paper’s rationale helps raise awareness about the negative effects of body image concerns, the risk of eating disorders, and more. The paper also highlights the professional help-seeking attitudes of Vietnamese youth.